FAMILY MEMBERS’ HISTORY ABOUT THE CARE PROVIDED TO A PERSON WITH A CHEMICAL ADDICTION - Miziara, Diandra Folquito Jorge; Nimtz, Miriam Aparecida; Kuznier, Tatiane Prette; Miranda, Fernanda Moura D’Almeida; Souza, Silvana Regina Rossi Kissula; Bais, Dulce Dirclair Huf; Paes, Marcio Roberto (Cogitare Enfermagem, 2022)
Objective: to know how family members experience the care provided to a person with a chemical addiction. Method: Hybrid Thematic Oral History, with four collaborators and having as locus a psychiatric hospital located in the city of Curitiba, Paraná, Brazil. Data collection took place between October and November 2020. The data were analyzed following the absolute transcription, textualization and transcreation steps. Results: two topics were revealed, namely: The family member’s experience regarding treatment of a person with a chemical addiction; and Spirituality and religiousness as support to deal with the challenges inherent to the chemical addiction. Conclusion: chemical addiction exerts a number of impacts on the family members, who suffer due to onset of this disease, leading to distress, frustration and sometimes hopelessness in the relatives. Various experiences regarding the same event can be useful as a reflection and warning for everyone about the importance of care targeted at the family members.